2010
DOI: 10.1186/1471-2407-10-194
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile and genomic alterations in colonic tumours induced by 1,2-dimethylhydrazine (DMH) in rats

Abstract: BackgroundAzoxymethane (AOM) or 1,2-dimethylhydrazine (DMH)-induced colon carcinogenesis in rats shares many phenotypical similarities with human sporadic colon cancer and is a reliable model for identifying chemopreventive agents. Genetic mutations relevant to human colon cancer have been described in this model, but comprehensive gene expression and genomic analysis have not been reported so far. Therefore, we applied genome-wide technologies to study variations in gene expression and genomic alterations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 52 publications
7
41
1
2
Order By: Relevance
“…NO reinforces angiogenesis by stimulating of cyclooxygenase which promotes the production of proangiogenic factors and prostaglandins. Femia et al [22] reported that DMH-induced colorectal cancer has high pro-inflammatory enzyme inducible nitric oxide synthase (iNOS) expression. Many researches report high iNOS activity in colon cancer [23-24] and support our findings.…”
Section: Discussionmentioning
confidence: 99%
“…NO reinforces angiogenesis by stimulating of cyclooxygenase which promotes the production of proangiogenic factors and prostaglandins. Femia et al [22] reported that DMH-induced colorectal cancer has high pro-inflammatory enzyme inducible nitric oxide synthase (iNOS) expression. Many researches report high iNOS activity in colon cancer [23-24] and support our findings.…”
Section: Discussionmentioning
confidence: 99%
“…4,9 PIRC (n 5 8) and wt (n 5 4) rats aged one month were analyzed with procedures previously described. 18 What's new? The majority of human colorectal cancers (CRCs) are associated with mutations in APC, which encodes the tumor suppressing APC protein.…”
Section: Semi-quantitative Rt-pcrmentioning
confidence: 99%
“…It is beleived that chronic infl ammation and repeated production of NO by iNOS leads to neoplastic transformation, a key step in the process of carcinogenesis. Increased expression of iNOS in DMH-induced group was probably due to a positive regulation of the NOS2 gene, which codes iNOS [12].…”
Section: Resultsmentioning
confidence: 99%